Emotional Contagion in Collaborative Virtual Reality Learning Experiences: An eSports Approach - Dirin, Amir; Nieminen, Marko; Laine, Teemu H.; Nieminen, Lassi; Ghalebani, Leila (EDUCATION AND INFORMATION TECHNOLOGIES, 2023)
Emotional contagion is an intriguing subject in many academic fields, and it is also relevant in collaborative learning where learners share a physical or virtual space. We aimed at exploring the possibilities of motivating, fascinating, and experiential elements of virtual reality (VR) in a collaborative learning context, with a focus on emotional contagion. We adopted the eSports mode as a competency development strategy in collaborative learning, using VR to evaluate emotional contagion that is invoked between the presenters and spectators. For this purpose, we created a VR application (HHVR) that allows freshmen students to learn about the premises and academic life at a university. We then divided 43 adult participants into presenters ( N = 9) and spectators ( N = 34); the presenters experienced the HHVR application first-hand, whereas the spectators watched the experience through a monitor. We used a questionnaire and semi-structured interviews to measure what feelings of being — existential feelings that affect the way we react to the world — the participants experienced. The collected data were analyzed by Principal Component Analysis and qualitative data coding and the results revealed emotional contagion; the spectators who followed the presenters on a monitor showed similar emotional engagement with the presenters who used the application. In conclusion, the proposed eSports mode can be a useful pedagogical technique in the context of collaborative learning with VR, as it engages emotionally both the presenters and spectators. These findings can be helpful for designing emotionally engaging collaborative learning experiences with VR and for conducting group-based UX evaluations of VR applications.